Ecological assessment of a temperate river system using biomonitoring techniques: a case study of the Bloukrans River system, South Africa - Magadze, Tinotenda (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Escalating pressures from growing human populations and environmental impacts increasingly imperil freshwater ecosystems. The Bloukrans River, which drains an urbanised and agricultural catchment in the Eastern Cape province of South Africa, is no exception. Detailed knowledge of the structure and function of the aquatic ecosystems is required in order to create models and matrices that predict, guide assessment and direct intervention on ecological integrity and water quality management in these systems. The main objectives of this research were to: examine the effects of urbanization on the benthic macroinvertebrate functional feeding guild structure among different stream orders; determine if benthic diatoms can be used as effective and reliable indicators of ionic composition and conductivity in different stream order categories and finally; to evaluate the applicability of the South African Diatom Index (SADI) and other indices in the Eastern Cape region of South Africa. Field studies were carried out to explore temporal patterns in community structure (macroinvertebrates and diatoms) and ecosystem function related to land-use patterns, instream habitat availability, and water quality parameters in the Bloukrans River system across four study periods: February (summer) and July (winter) 2016 and February (summer) and May/July (winter) 2018. The study was conducted along a gradient of impacts from less impacted agricultural headwaters to highly impacted urban sites located immediately downstream of the city of Makhanda. Macroinvertebrates were separated into functional feeding groups (FFGs) (i.e. collector-gatherer, collector-filterer, scraper, shredder, and predator) which were then used to assess the effects of selected physico-chemical variables and riparian zone condition on FFG organization. Collector-gatherers were the most abundant in the Bloukrans River and represented 71.3 % of the macroinvertebrate assemblages. Stream order 1species such as Nitzschia palea, Gomphonema parvulum, Tryblionella apiculata, Diploneis vulgaris and Staurosira elliptica. Multivariate analysis (Canonical correspondence analysis (CCA)) indicated that differences in diatom community assemblages were best explained by calcium, magnesium, pH, phosphate, nitrate, dissolved oxygen, sediment nitrate, conductivity and salinity. These results indicate that diatoms can be used as bioindicators for monitoring highly impacted river systems and to also further examine pollution gradients and impacts of specific/point pollution sources. In order to further test the application of diatom indices, nine sites with contrasting water quality were sampled along the length river system in February, May and July 2018. Diatom-based indices incorporated in OMNIDIA software were applied to assess the integrity of the water quality as indicated by diatom communities. For comparative purposes, several foreign indices (e.g. the trophic diatom index (TDI), the percentage pollution-tolerant valves (%PTV), biological diatom index (BDI)) and the South African Diatom Index (SADI) were used in the study. From the results, the Percentage Pollution-Tolerant Valves (%PTV) of most urban sites in the Bloukrans River was above the 20% limit indicating the presence of organic pollutants. Although the foreign diatom indices were applicable in the study, the SADI had significant correlations with most water quality variables (p < 0.05) compared to other indices such as Watanabe Index (WAT), Biological Index of Water Quality Trophic Index (BIWQ) and Trophic Index (TI)). These results support wider use of the SADI as an indicator of water quality conditions in South African river systems. Finally, the observed variations in diatom community structure and composition as a result of changes in water quality were broadly in agreement with the results of macroinvertebrate FFG structure indicating that the two biological indicators can, and should, be used as complementary techniques in the biomonitoring of rivers and streams in South Africa.
Keywords: Bloukrans River; Ecological assessment (Biology) -- South Africa; Stream ecology -- South Africa; Rivers -- Environmental aspects -- South Africa; Benthic animals -- Effect of human beings on -- South Africa; Water quality biological assessment -- South Africa; Diatoms -- South Africa -- Data processing